Effect of coconut waste and chicken manure on the growth and yield of caisim (Brassica juncea L) - Bobot Sudoyo; Herdhata Agusta (Journal of Agrosociology and Sustainability, 2026)
Background: Coconut waste and chicken manure present innovative solutions for enhancing the growth and yield of caisim crops. Cocopeat is one of the organic growing media that is increasingly popular in modern horticultural cultivation. Utilizing coconut waste as a planting medium improves aeration and water retention, both of which are crucial for the development of caisim roots. Methods: This study used a randomized group design with five soil treatments to evaluate caisim growth. Parameters included plant height, leaf number, biomass, and soil nutrient content, analyzed using ANOVA and DMRT. Findings: The study revealed that the P3 treatment (soil:cocopeat:chicken manure = 1:1:1) produced the tallest caisim plants, highest leaf number, and greatest fresh weight. Nutrient balance and organic matter improved plant growth, transpiration, and stomatal conductance, while excessive nitrates and pH deviations reduced leaf formation. Total dissolved solids and electrical conductivity positively correlated with growth, highlighting the importance of balanced planting media for optimal vegetative development and biomass accumulation. Conclusion: The results revealed that the composition of the planting medium significantly influenced morphological growth, nutrient content, and the correlation between various growth parameters of caisim plants. Novelty/Originality of this article: The treatments P3 (soil: cocopeat: chicken manure in a ratio of 1:1:1) and P4 (1:2:1) yielded the best outcomes, resulting in increased plant height, fresh weight, and nutrient content, including nitrogen, phosphorus, and potassium. Additionally, these treatments produced optimal Total Dissolved Solids (TDS) and Electrical Conductivity (EC) values, which are essential for effective nutrient absorption.